A Reassessment of the Indian Heavy Industrialization Strategy - Upadhyay, Vrajaindra (My University, 1984)
The industrial strategy which emphasizes heavy industries in the Indian economy has been the subject of a major controversy. This study reassesses the implications of the heavy industries strategy. The study has been conducted within the framework of a five-year plan using a dynamic multisectoral linear programming model.
Several experiments are performed with the model under varied assumptions and restrictions. The results of the various experiments are then compared with the results of the bench mark case and among themselves. The capacity constraint is introduced in the model in order to ensure non-transferability of capital between sectors and periods and to prevent consumption of capital. The land constraint is introduced in order to evaluate the effect of the limited availability of land on economic growth. To assess the impact of the use of modern techniques in agriculture on economic growth, in some experiments of the model Japanese agricultural input/output and capital/output coefficients are used. In order to examine the issues related to the choices between present and future consumption, three different objective functions are used in this study.
The main effect of the capacity constraint is to strengthen the equipment sector. The constraint raises the deliveries made by the equipment sector for the purpose of investment. The increased investment activity is provided for by increase in domestic production of equipment goods. The burden of the growth in the equipment sector caused by the capacity constraint is generally borne by the services sector. This is especially the case when the agricultural sector uses traditional technology.
The results of our study show that it is mainly the capital goods sectors which benefit from the assumption of limited land availability. Our findings thus provide a justification for the heavy industries strategy in the Indian case where the assumption of limited land availability is very reasonable.
The application of the Japanese agricultural technology in Indian agriculture raises agricultural production, however, its effect on consumption and on other sectors of the economy may not be favourable if the technological transformation is limited to the agricultural sector alone.
The main effect of inclusion of the consumption stream of the post-plan period, or of inclusion of investment, in the objective function is to strengthen the equipment sector. The strengthening of the equipment sector comes mainly at the cost of the agricultural sector.
Keywords: Philosophy; Philosophy